Mengembangkan Kematangan Sosial pada Anak melalui Outbond - Yeniar Indriana D.; Tri Windarti (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2008)
Abstract: In the education world, outbound education is a children’s training in the context of natural world as a learning instrument. This type of education gives children survival competencies integrated with environmental knowledge and other supported learning materials The  supported learning materials are leadership, cooperation, aotonomy, self confidence, motivating skills, creativity building, responsibility sense, and problem solving skills.  Also in the social children interactions during outboun process, the trainers can develop children’s social maturity.